Subtitusi Membran Polimer dengan Limbah Puntung Rokok Untuk Mencegah Emulsi Minyak dan Air pada Limbah Cair Industri - Mahogra Teja Mutthohar; Fatih Nur Shofwan Khoironi; Yuni Hidayani; Agus Widayoko (Jurnal Integrasi Sains dan Quran, 2026)
Oily waste is one of the most difficult types of waste to manage due to the lack of filtration facilities for petrochemical industry waste. According to the Ministry of Environment and Forestry, the average amount of oil is 1000-2000 mg/L in industrial liquid waste, which has a negative impact on the aquatic environment and other biota. On the other hand, in 2020, tobacco consumption reached 322 billion sticks, producing approximately 107.3 tons of cigarette butt waste. Cigarette butts contain cellulose acetate, making them solid waste that is difficult to decompose naturally. However, cigarette butt filters, which are rich in cellulose acetate, have great potential as an alternative raw material for membrane technology. This study aims to develop polymer membranes based on recycled cigarette butt waste as an environmentally friendly membrane system for sustainable living, by evaluating the effectiveness of water filtration using these membranes with a minimum permeation flux indicator of 400 L/m²·hour and reducing membrane production costs by ≤ 30% compared to conventional membranes. The method used is descriptive with a quantitative approach, focusing on the utilization of cigarette butt waste as a polymer membrane. Data collection was carried out through experiments, observations, and literature studies. From the tests conducted, the permeation flux test was 474,6-588,5 L/m²/hour, referring to Widiasa’s (2014) research. The water toxicity test with a pH of 7 met SNI 06-6989.11-2004, and the durability test showed that the membrane could be used three times.